ANALISIS CLUSTER INDEKS PEMBANGUNAN MANUSIA DENGAN MENGGUNAKAN METODE HIERARKI PADA KABUPATEN/KOTA DI PROVINSI BANTEN - Sukmawati, Sri; Alam, Tubagus Bakhrul; Rahmatullah, Asep; Abdullah, Syarif; Sukandar, Rani Septiani (LPPM Universitas Bina Bangsa, 2024)
A high Human Development Index (HDI) greatly determines the ability of the population to absorb and manage sources of economic growth, both in relation to technology and institutions as an important means to achieve economic growth. The purpose of this study is to group districts/cities in Banten Province and find out the characteristics of each group based on the Human Development Index indicators. HDI is a composite index that shows the achievement of successful human development in a region. The research data used is secondary data with the population of all districts/cities in Banten Province. Cluster analysis is a technique used to group objects into different groups. The results of the study were obtained in 2 clusters using the single linkage, average linkage, and complete linkage methods which included the first cluster, namely Tangerang City, Tangerang Regency, Serang City, Pandeglang Regency, Serang Regency, Lebak Regency, and Cilegon City, while the second cluster was Tangerang City and South Tangerang City